2001
DOI: 10.1177/00139160121972864
|View full text |Cite
|
Sign up to set email alerts
|

Coping with add

Abstract: Attention Restoration Theory suggests that contact with nature supports attentional functioning, and a number of studies have found contact with everyday nature to be related to attention in adults. Is contact with everyday nature also related to the attentional functioning of children? This question was addressed through a study focusing on children with Attention Deficit Disorder (ADD). This study examined the relationship between children’s nature exposure through leisure activities and their attentional fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(98 citation statements)
references
References 23 publications
4
82
0
2
Order By: Relevance
“…It may not be surprising that physical health can be greatly improved by spending time outdoors (e.g., Brymer, Cuddihy & Sharma-Brymer, 2010;Frumkin, 2001), while outdoor play has been found to encourage the healthy development of children's motor skills (Fjørtoft, 2001). Some evidence even suggests that playing in greenspace can help reduce symptoms of ADD in children (Taylor, Kuo & Sullivan, 2001). Individuals do not necessarily need to be immersed in nature; even the presence of ornamental indoor plants is suggested to encourage recovery from surgery (Park & Mattson, 2009).…”
Section: Nature Contact and Connectednessmentioning
confidence: 99%
“…It may not be surprising that physical health can be greatly improved by spending time outdoors (e.g., Brymer, Cuddihy & Sharma-Brymer, 2010;Frumkin, 2001), while outdoor play has been found to encourage the healthy development of children's motor skills (Fjørtoft, 2001). Some evidence even suggests that playing in greenspace can help reduce symptoms of ADD in children (Taylor, Kuo & Sullivan, 2001). Individuals do not necessarily need to be immersed in nature; even the presence of ornamental indoor plants is suggested to encourage recovery from surgery (Park & Mattson, 2009).…”
Section: Nature Contact and Connectednessmentioning
confidence: 99%
“…Recently, several studies have suggested that exposure to outdoor activities may, at least temporarily, improve attention and concentration (Faber, Taylor & Kuo, 2009). This novel approach is based upon Attention Restoration Theory (ART) which posits that there are two types of attention-voluntary and involuntary (Faber Taylor et al, 2001;Faber Taylor & Kuo, 2009;Tennessen & Cimprich, 1995). Green Space is said to alleviate fatigued voluntary attention by drawing from involuntary attention (Faber Taylor & Kuo, 2009;Tennessen & Cimprich, 1995).…”
Section: Walking In a Natural Winter Setting To Relieve Attention Fatmentioning
confidence: 99%
“…Reviews of this empirical literature are plentiful [8][9][10][11][12][13][14][15][16]. Findings from this work suggest that even relatively short exposures to natural environments can have a significant effect on psychological health, leading to improvements in mood [17][18], attentional functioning [19][20][21][22][23][24], coping abilities [25], and overall well-being [26].…”
Section: Introductionmentioning
confidence: 99%